1992
DOI: 10.1002/jobm.3620320504
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism of gluconate in Escherichia coli: A study in continuous culture

Abstract: The gluconate metabolism in Escherichia coli involves duplicate activities of transport and phosphorylation for gluconate. In both cases, these activities can be differentiated in vifro by their different affinities for the substrate. In addition, the two gluconokinases can be differentiated by their heat sensitivities. The technique of continuous culture was used to investigate the influence of the growth rate on this metabolism in an E. coli HfrG6 strain during gluconate-limited growth under conditions of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Moreover, in gluconate-limited mineral medium continuous culture, the total gluconate kinase activity, consisting of GntV at very low dilution rates (D), is gradually repressed as the induction of GntK increases as a consequence of the progressive increase of D and corresponding increment in the concentration of limiting substrate. These findings indicated that gntV induction, contrary to that of gntK, occurs mainly at low gluconate concentrations (Coello and Istúriz, 1992).…”
Section: Introductionmentioning
confidence: 82%
“…Moreover, in gluconate-limited mineral medium continuous culture, the total gluconate kinase activity, consisting of GntV at very low dilution rates (D), is gradually repressed as the induction of GntK increases as a consequence of the progressive increase of D and corresponding increment in the concentration of limiting substrate. These findings indicated that gntV induction, contrary to that of gntK, occurs mainly at low gluconate concentrations (Coello and Istúriz, 1992).…”
Section: Introductionmentioning
confidence: 82%
“…Since GntV is induced together with GntI activities when cells grow in presence of gluconate (ISTÚRIZ et al 1986, COELLO andISTÚRIZ 1992), or in presence of an idonate supplemented medium (BAUSCH et al 1998), there should be some coordination in the expression of these activities. Since GntV is induced together with GntI activities when cells grow in presence of gluconate (ISTÚRIZ et al 1986, COELLO andISTÚRIZ 1992), or in presence of an idonate supplemented medium (BAUSCH et al 1998), there should be some coordination in the expression of these activities.…”
mentioning
confidence: 99%
“…The GntII system, a subsidiary system for gluconate transport and phosphorylation, located in the 96-min region, includes the gntS gene, encoding another high-affinity transport system, and the gntV gene, encoding a thermosensitive glucokinase (15). Various observations have suggested that the genes of the GntI and the GntII systems are differentially regulated (1,5,19). The GntI system is specifically induced by gluconate and is regulated by the gntR gene (also located in the 75-min region) product, a repressor of the genes of the GntI system and the Entner-Doudoroff pathway but not of the genes of the GntII system (9, 19, 32).…”
mentioning
confidence: 99%